Hipertensão portal por trombose de veia porta em crianças: eficiência da abordagem cirúrgica - BAYMA, Lohrane Rosa (2019)
Thrombosis of the portal vein causes a decrease in flow at this location by mechanical or functional obstruction. It can extend to the liver and occlude the intrahepatic portal branches or even superior and/or splenic mesenteric veins. Portal vein thrombosis is related to hypercoagulability, dehydration, infection of the abdominal cavity or malformations of the portal system. The obstruction of the portal vein induces the formation of collateral circulation that can determine esophageal and gastric varices. Surgical intervention is an option for the treatment of children with hepatic vein thrombosis without liver disease and it is not cured by clinical/endoscopic treatment, but it is not an attempt to curb or bleed or relapse, which entails great morbidity and mortality. The objective of this study was to demonstrate the efficiency of the surgical intervention, that is, to avoid bleeding by portal hypertension. The present study analyzes the evolution of children undergoing a surgical treatment, when there was difficulty in clinical/endoscopic treatment, with a transversal analytical approach. The study was conducted at the Pediatric Administration and Surgery Group of the Santa Casa de Misericórdia do Pará (Belém, Pará) from 2007 to 2015 and includes data from 7 patients. A predominance of females was observed, a mean of 7.86 years on the occasion of the first consultation and manifestation of the first symptoms (digestive hemorrhage), diagnosis of portal venous thrombosis isolated in 5 of the patients, also associated with an intrahepatic involvement of the Portal branches. We also evaluated the need for blood products. More frequent surgery for distal splenorenal shunt. We analyzed the recurrence of gastrointestinal bleeding in 2 cases and shunt thrombosis also in 2. It was concluded that despite the recognized superiority of Rex shunt as a technique for primary and secondary profiles of digestive hemorrhages due to portal obstruction, this method was not applied in the Sample of the work, possibly due to delay in notifications and, mainly, due to specific anatomical restrictions in each case (intrahepatic involvement of the portal branches for example); Surgical treatment was effective in preventing new episodes of hemorrhage in 71% of patients, a period of prolonged postoperative follow-up